Monitoramento de um processo de lixiviação de cobre em placas de circuito impresso por meio da análise direta de sólidos e uso de Laser-Induced Breakdown Spectroscopy (LIBS) - Garcia, José Augusto (2021)
This PhD thesis was developed at CTI Renato Archer, Campinas-SP and was based on a hydrometallurgical process, on an industrial scale, applied to the recovery of metals in discarded printed circuit boards (PCBs). The objectives of this work were the optimization and monitoring of a specific step of the hydrometallurgical process, that is, the leaching step of Cu present in PCBs. In the first stage of the studies, a fractional factorial design of experiments (25-1) was carried out, resulting in 16 experiments with the objective of evaluating and optimizing the copper leaching process. The variables studied were: i) concentration of NH4OH (mol.L-1); ii) concentration of (NH4)2SO4 (mol.L-1); iii) flow of O2 (L.h-1); iv) leaching time (h); v) solid/liquid ratio (kg.L-1). In the factorial design of experiments responses, the concepts of mass balance were used and the conversion factors of solid state metals to a solution (Xm) were calculated. In this way, the Xm of Cu and Au present in the ‘discarded PCBs were calculated, in addition, because it is an optimization of an industrial scale process, another answer evaluated was the operational cost of the process for Cu extraction (OCPCu). With the use of chemometric tools, it is concluded, therefore, that the proposed chemical system can present a Cu extraction with approximately 89% efficiency, high selectivity and an acceptable operating cost if the following process parameters are obeyed: i) [NH4OH] = 6,5 mol.L-1; ii) [(NH4)2SO4] = 2,0 mol.L-1; iii) flow of O2 = 240 L.h-1; iv) leaching time = 3 horas; v) solid/liquid ratio = 0,1 kg.L-1. In another stage of the work, an alternative analytical method to control the copper leaching step in PCBs was evaluated, using LIBS. After analyzing the LIBS and properly processing the data obtained, contour graphs were generated with the intensity values of the Cu spectral signal, at 324,754 nm, for each sampling point (laser pulse), enabling the mapping of the surface of the sample analyzed based on the presence of Cu. It is concluded that the combination of LIBS with chemometric tools for the treatment of spectral data and the use of signal intensity maps to compare different Cu extraction conditions proved to be a fast and efficient method for the evaluation of the leaching process, with the advantage of requiring a relatively less complex sample preparation compared to determinations performed at ICP OES